Answer: A) 4.8 CM
Step-by-step explanation:
(2/5) of (2/3) of students = 4/15 of students study French. Then 1-(4/15) = 11/15 of students do not study French. The ratio you want is
(4/15):(11/15) = 4:11
_____
In a math expression "of" means "times".
Using logarithms property of log(x)+log(y)=log(xy)
so here, you can sum the equation to;
![log((x+6)*(x-6))=2](https://tex.z-dn.net/?f=log%28%28x%2B6%29%2A%28x-6%29%29%3D2)
so you can simply say that;
![log_{8}((x+6)( x-6))=2](https://tex.z-dn.net/?f=%20log_%7B8%7D%28%28x%2B6%29%28%20x-6%29%29%3D2%20)
and by multiplying (x+6)*(x-6)
![log_{8}(x^2-36)=2](https://tex.z-dn.net/?f=log_%7B8%7D%28x%5E2-36%29%3D2)
and as you know also that;
![a^{b}=c](https://tex.z-dn.net/?f=%20a%5E%7Bb%7D%3Dc%20)
is same as
![log _{a}c=b](https://tex.z-dn.net/?f=log%20_%7Ba%7Dc%3Db%20)
so you can simply state it as;
![8^2=x^2-36 64=x^2-36 64+36=x^2 x^2=100 x=10](https://tex.z-dn.net/?f=8%5E2%3Dx%5E2-36%0A64%3Dx%5E2-36%0A64%2B36%3Dx%5E2%0Ax%5E2%3D100%0Ax%3D10)
And you can check your work by substituting with 10 instead of x in the original function.
Hope this helps!
|a| = -a for a < 0
|a| = a for a ≥ 0
examples:
|-1| = -(-1) = 1; |-4| = -(-4) = 4; |-0.1| = 0.1; |-109| = 109
|7| = 7; |19| = 19; |0| = 0
- |-7 + 4| = - |-3| = - (3) = -3
Answer: -|-7 + 4| = -3
<span>–36, –32, –28, –24 This is an arithmetic sequence because each term has the same difference from the preceding term, called the common difference, d...
-32--36=-28--32=-24--28=4 So 4 is d, the common difference.
The sequence of any arithmetic sequence has the form:
a(n)=a+d(n-1), a=first term, d=common difference, n=term number...in this case we have:
a(n)=-36+4(n-1)
a(n)=-36+4n-4
a(n)=4n-40 so the 29th term is:
a(29)=4(29)-40
a(29)=116-40
a(29)=76
...
distance=velocity * time
d=vt we want to find t so
t=d/v and in this case:
t=234/70
t=(210+24)/70
t=3hr+(60*24)/70
t=3hr+20min+34sec so
t≈3hr 20min
...
This is an arithmetic sequence...100,150,200...
The sum of an arithmetic sequence will always be the average of the first and last terms times the number of terms....
the rule for the sequence is:
a(n)=a+d(n-1), a(n)=100+50d-50, a(n)=50n+50
Now we know the nth term is 50n+50, and we also know the first term is 100 so:
s(n)=n(100+50n+50)/2 and we want to know the sum of the first 10 terms so
s(10)=10(100+500+50)/2
s(10)=$3250
...
The first two terms are 2 and 4 so:
a(n)=2+2(n-1)
a(n)=2+2n-2
a(n)=2n
a(10)=20
...
You could do synthetic or long division, but you also could just use the fact that the factor being (x+8) should indicate a zero for the function when x=-8. If f(x) could be divided by (x+8) the value of y(-8) would equal zero, however calculating y(-8)=-10 so that would be the remainder if you did the division.</span>